Police/Militia in (Post-)Soviet Popular Culture (Towards a Historical Iconography of Power) - D. V. Popov (Социология власти)
The idea of the police as a "good order” from the Polizeiwissenschaft of absolutism was developed in the biopolitical model of caring for the population of the Modern era, engaged in ensuring safety and well-being. Being a product of mass society, the modern state has focused on influencing public opinion. In the XIX-XX centuries, there was a counter-movement of police supervision and art which gave rise to 'police aesthetics'. Cinematography was an effective means of forming a desirable image of the Soviet militia in the post-war period of normalization of public life. By contributing to the Soviet myth of developed socialism, militia cinema contributed to a screento-life transfer of a new norm of trust between representatives of power and citizens. This constructivist cinema involved the viewer in the cinematic reality by likening them to the main character, a militiaman who acts as a moral guide. In addition to forming the image of the 'familial militia', intellectual militia cinema — with its focus on professionalism — is actively developing. The most popular version of the latter is militia cinema that thematizes the moral rightness of militia officers fighting crime in the name of Soviet citizens. Involvement in the cinematic reality through assimilation, novelty, memory, and imagination included the romanticization of the historical events of the revolution. Militia cinema was inverted during the years of the perestroika. It exploited the effect of novelty associated with the viewer's immersion in emerging market relations. The viewer's interest was focused on the wrong, criminal, side of public life. Crime is romanticized, the militia is stigmatized. From constructing the myth of cooperation between the government and the population, militia cinema moves on to deconstructing the myth, achieving an effect of denigration. The fashion for American cinema brings elements of action, thriller, horror. The viewer is no longer included in the imperious project of transforming reality; they are attracted by the illusion, the spectacle. The latest police cinema, overcoming total deconstructionism, is busy reconstructing the spirit of Soviet militia cinema in modern settings. Oscillating between the intention to generate positive images of the police and the demonstration of the "truth of life”, modern police cinema contains the natal shoots of a new cinema in which the image of the police is important for the normalization of public life.